Multimorbidity among midlife women in India: well-being beyond reproductive age - Parul Puri; Abhinav Sinha; Pranab Mahapatra; Sanghamitra Pati (BMC, 2022)
Abstract Background Currently, inequality in life expectancy across gender makes women outlive men. Adult women transit towards menopause around midlife accompanied by a series of natural physiological changes leading to several conditions such as osteoporosis, depression, and urinary incontinence, which puts them at a higher risk of having multimorbidity. Multimorbidity is often associated with poorer quality of life, leading to deteriorated work productivity and associated economic loss in midlife. Hence, this study aimed to determine the magnitude and correlates of early onset of multimorbidity and explore its linkages with health-related quality of life (HRQoL) among middle-aged women in India. Methods We have utilized data from the first round of the Longitudinal Ageing Study in India, 2017-19. We included women aged 45-65 years (n = 23,951) for analysis. Descriptive data were presented. An ordered logistic regression was conducted and proportional odds were reported to identify the correlates of multimorbidity. To explore the linkages between multimorbidity and selected indicators of HRQoL, an array of regression models were executed. Results Multimorbidity was reported amongst 29.8% of women in midlife. Chandigarh (PR-54.8 PER 100 women) and Punjab (PR-52.8 per 100 women) reported the highest prevalence of multimorbidity. Women with multimorbidity reported compromised HRQoL indicators such as self-rated health, work-limiting health conditions, mobility, and activities of daily living. Conclusions Multimorbidity is increasingly prevalent in midlife women associated with inferior quality of life. The reproductive health programs for women should consist of midlife women focusing on multimorbidity and overall well-being.